Perspektif Etika Kritis-Liberatif Dalam Teologi Pembebasan Islam - Sutikno Sutikno (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2019)
This study focuses the construction of liberative and critical ethics in Islamic theology of liberation in the wave of liberal democracy from paradigm of capitalism dan neoliberalism. The practice of liberal democracy in general election and public policy centered to capital that implicate pragmatic, instrumentalist and manipulative political cultures. Those implications rise largest implications of public rights which have to be implemented in public politicies. Critical and liberative ethics was qualitative type with library research and uses ideological and theological approaches. The results of this study that practice of liberal democracy in contemporary political life was a structure that rise continuity and change. Critical and liberative ethics have to intervention both agenda of democracy and public policy started in planning untill action. The process of political education based on critical and liberative ethics have to be actualized by each actor and political institution untill make balance between people and state relations. Critical and liberative ethics have tobe a foundation of discourse in public sphere communications of public sphere which to appreciates principles of egalitarianism and populism untill make a social change in society.